Estudo comparativo de análise numérica aplicada a placas esconsas - Nóbrega, Francisco Seraphico Ferraz de (1972)
The purpose of this work is the development of study of two numerical methods, the finite difference and the finite element method, as applied to the calculation of simply supported skew plates. Convergence towards the analytic solution has been examined for different skew angles, and computed the increase of time of calculation due to the mesh refinement. An automatic program of finite difference for oblique mesh has been written and two automatic programs available have been employed. One developed by Prof. ALCEBIADES VASCONCELLOS FILHO in his Ph.D. thesis at COPPE in 1970, and ICES STRUDL II version 1969 developed at Massachusetts Institute of Technology. There have been used non conforming triangular elements, with three nodal points and nine nodal displacements. The method of finite differences has showed better results and in both methods the convergence decreases along with the increase of the skew angle.